A Highly Active Manganese Catalyst for Enantioselective Ketone and Ester Hydrogenation. Issue 21 (20th April 2017) - Widegren, Magnus B.; Harkness, Gavin J.; Slawin, Alexandra M. Z.; Cordes, David B.; Clarke, Matthew L.
Abstract: A new hydrogenation catalyst based on a manganese complex of a chiral P, N, N ligand has been found to be especially active for the hydrogenation of esters down to 0.1 mol % catalyst loading, and gives up to 97 % ee in the hydrogenation of pro‐chiral deactivated ketones at 30–50 °C. Abstract : Non‐precious metal for valuable catalysis : A new manganese catalyst for enantioselective ketone hydrogenation has been developed (see scheme). This catalyst also hydrogenates esters at low catalyst loadings for an earth‐abundant metal system.